A systematic review of circulating markers in primary chronic venous insufficiency. (October 2014) - Smith, Ross K; Golledge, Jonathan
Objectives: The etiology of primary chronic venous insufficiency is poorly understood. This systematic review aimed to summarize published evidence assessing the association of circulating markers with primary chronic venous insufficiency. Methods: A search was undertaken through the PubMed database using the terms "venous insufficiency" and "biological marker" or "plasma" or "serum". Search limits included English language, human subjects and studies with publication dates from 1994. Studies which classified patients using the Clinical-Etiology-Anatomy-Pathophysiology system of venous disease were analyzed. Results: Seventeen studies were included, which have examined > 60 different biomarkers. A total of 13 markers were assessed in >1 study with the number of primary chronic venous insufficiency cases ranging from 41 to 244 and the number of controls ranging from 30 to 144 in these studies. Circulating estradiol, homocysteine and vascular endothelial growth factor were the most consistently associated with primary chronic venous insufficiency. Conclusions: Whilst a number of studies have examined biomarkers associated with primary chronic venous insufficiency, further studies are required using improved and standardized approaches on larger populations. Biomarker research may increase pathogenic knowledge and result in opportunities to decrease chronic venous insufficiency burden.